Long-term, open-label, safety study of once-daily ropinirole extended/prolonged release in early and advanced Parkinson's disease. (2nd January 2016) - Makumi, Clare W.; Asgharian, Afsaneh; Ellis, Jeffrey; Shaikh, Soraya; Jimenez, Teri; VanMeter, Susan
Abstract : Long-term safety of once-daily ropinirole extended/prolonged release (ropinirole XL/PR) was evaluated in subjects with early and advanced Parkinson's disease (PD) in this study, 101468/248. Subjects ( n = 419) who completed one of three prior studies evaluating ropinirole XL/PR for the treatment of PD were enrolled in this open-label, multicenter, extension study, and were to be followed for up to 73 months. Ropinirole XL/PR was titrated/continued, and adjusted as appropriate during the maintenance phase (maximum 24 mg/d). Levodopa (L-dopa) and other nondopamine agonist PD medications were permitted. Safety outcomes that were investigated included frequency of adverse events (AEs). Subjects' preference regarding once daily versus three times daily study medication regimens was also investigated in a subset of the study population. The median duration of ropinirole XL/PR exposure was 1275 d. Most subjects (87%) reported at least one AE, with the most common (≥ 10%) AEs being, back pain (14%), hallucinations (13%), somnolence (11%) and peripheral edema (11%). Twenty-five percent of subjects discontinued the study prematurely due to an AE during the treatment period. Long-term treatment with ropinirole XL/PR was not associated with any new or unexpected safety concerns in patients with early and advanced PD, and a majority of subjects preferred the once-daily dosing regimen.